MENGGULUNG TRADISI: REINTERPRETASI NASI GULUNG WONOCOLO SEBAGAI WARISAN BUDAYA TAK BENDA - Oktavianus Cahya Anggara; Dinda Nur Safitri; Mustika Ayu Aprilia Susanti; Siti Alfiana Dzakia; Hafidh Ash Shodiqi (LP2M UIN Abdul Muthalib Sangadji Ambon, 2025)
This study aims to analyze the reinterpretation of Nasi Gulung Wonocolo as an effort to preserve intangible cultural heritage in the midst of modernization and changing tastes within the community. The study employs a descriptive qualitative approach that includes participatory observation methods, in-depth interviews, and documentation conducted in Wonocolo Village, Bojonegoro Regency. The results of the study show that reinterpretation through innovation in taste, packaging, and promotional strategies is able to maintain traditional values while adapting them to the needs of modern society. Nasi Guroll's integration into the edutourism concept of the Wonocolo Geopark effectively strengthens local cultural identity, increases community participation, and encourages the growth of a culinary-based creative economy. This research contributes to the development of ethnoculinary studies and adaptive cultural preservation, as well as provides practical recommendations for tourism managers and local governments in optimizing the potential of traditional culinary as a sustainable tourism attraction. Further research is suggested to review aspects of digital marketing and cross-sector collaboration to expand the reach of local culinary promotion